Determinants of Contraceptive Use among Muslim Women in Mbale City in the Eastern Region of Uganda - Kauthara Yudaya Namirembe; Naziru Rashid; Kharim Mwebaza Muluya; Abdulmujeeb Babatuunde Aremu; Swaibu Zziwa; Twaha Mafabi; Emmanuel Serioni; Shamim Babirye; Lukia Hamid Namaganda (International Journal of Human and Health Sciences (IJHHS), 2026)
Family planning is broadly acknowledged as a fundamental approach in public health for enhancing maternal and child health, remarkably preventing 32% of maternal deaths and 10% of child deaths. Lower levels of contraceptive uptake are observed among Muslim women than women of other faiths. This study investigated the determinants of contraceptive use among Muslim women of child bearing age in Mbale city in Uganda. This communitybased cross-sectional study was conducted among 374 Muslim women using intervieweradministered electronic questionnaires. The mean age of the participants was 338.8 years. The proportion of Muslim women who were currently using contraceptives was 32%. The associated factors included acceptability of family planning in the community (AOR=2.2, 95% CI: 1.104–4.314, p=0.025), desire to have more children later (AOR=6.8, 95% CI: 2.646–17.583, p